2022
DOI: 10.1016/j.stemcr.2021.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling reduced contractility and impaired desmosome assembly due to plakophilin-2 deficiency using isogenic iPS cell-derived cardiomyocytes

Abstract: Loss-of-function mutations in PKP2, which encodes plakophilin-2, cause arrhythmogenic cardiomyopathy (AC). Restoration of deficient molecules can serve as upstream therapy, thereby requiring a human model that recapitulates disease pathology and provides distinct readouts in phenotypic analysis for proof of concept for gene replacement therapy. Here, we generated isogenic induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) with precisely adjusted expression of plakophilin-2 from a patient with AC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…Among the desmosomal genes, mutations in PKP2 are most frequently identified in patients with AC[ 11 , 37 - 39 ], and have been extensively studied using patient-derived iPSC-CMs compared to other desmosomal genes ( DSG2 [ 30 , 40 , 41 ], DSP [ 42 , 43 ], and DSC2 [ 44 , 45 ]). Various clinical phenotypes and pathological characteristics observed in patients with AC harboring PKP2 mutations, downregulated desmosomal protein expression, upregulated lipogenesis, and increased apoptosis in heart tissues have been recapitulated using genetically engineered mouse models[ 11 ] and human cardiomyocytes differentiated from iPSCs[ 46 - 54 ] (Table 1 ). Most known mutations of PKP2 are heterozygous and are missense, nonsense, and frameshift mutations.…”
Section: Phenotypic Recapitulation Of Cardiomyopathy Caused By Pkp2 D...mentioning
confidence: 99%
See 4 more Smart Citations
“…Among the desmosomal genes, mutations in PKP2 are most frequently identified in patients with AC[ 11 , 37 - 39 ], and have been extensively studied using patient-derived iPSC-CMs compared to other desmosomal genes ( DSG2 [ 30 , 40 , 41 ], DSP [ 42 , 43 ], and DSC2 [ 44 , 45 ]). Various clinical phenotypes and pathological characteristics observed in patients with AC harboring PKP2 mutations, downregulated desmosomal protein expression, upregulated lipogenesis, and increased apoptosis in heart tissues have been recapitulated using genetically engineered mouse models[ 11 ] and human cardiomyocytes differentiated from iPSCs[ 46 - 54 ] (Table 1 ). Most known mutations of PKP2 are heterozygous and are missense, nonsense, and frameshift mutations.…”
Section: Phenotypic Recapitulation Of Cardiomyopathy Caused By Pkp2 D...mentioning
confidence: 99%
“…Studies on patient-derived iPSCs have identified that PKP2 variants are heterozygous missense[ 48 ], heterozygous frameshift[ 46 , 47 , 49 , 50 , 54 ], homozygous frameshift[ 47 , 51 ], compound heterozygous, and frameshift[ 52 ] mutations. Disease-specific iPSCs are generated from fibroblasts[ 46 - 48 , 51 ], keratinocytes[ 49 ], adipose tissue-derived stromal cells[ 52 ], and peripheral blood mononuclear cells[ 54 ], whereas control iPSCs are generated from healthy subjects[ 46 - 49 , 51 , 52 ], human embryonic stem cells[ 50 ], or isogenic cells engineered from patient-derived iPSCs using genome editing[ 54 ]. Genome editing allows disease modeling by introducing heterozygous and homozygous frameshift mutations in wild-type iPSC lines[ 53 ].…”
Section: Phenotypic Recapitulation Of Cardiomyopathy Caused By Pkp2 D...mentioning
confidence: 99%
See 3 more Smart Citations